2016
DOI: 10.4049/jimmunol.1600883
|View full text |Cite
|
Sign up to set email alerts
|

Water-in-Oil–Only Adjuvants Selectively Promote T Follicular Helper Cell Polarization through a Type I IFN and IL-6–Dependent Pathway

Abstract: T follicular helper (Tfh) cells are a subset of CD4+ T lymphocytes that promote the development of humoral immunity. While the triggers required for the differentiation of the other major T helper subsets are well defined, those responsible for Tfh responses are still poorly understood. We determined that mice immunized with either peptide or protein antigens emulsified in incomplete Freund’s adjuvant or related water-in-oil adjuvants develop a highly polarized response in which the majority of the antigen-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 32 publications
3
31
1
Order By: Relevance
“…Although we could not detect type I IFN induction at the time point examined in LNs of mice with CIA, TBK‐1 inhibition has been shown to reduce the type I IFN signature and alleviate disease in the three‐prime repair exonuclease 1–knockout murine model of SLE, through inhibition of the cGAS/STING pathway . Other studies demonstrate synergies between IL‐6 and type I IFN by driving optimal Tfh cell polarization and type I IFN–dependent IL‐6 induction in DCs that supports GC‐driven affinity maturation of antibodies . Taken together, we propose that TBK‐1 inhibition reduces production of cytokines associated with humoral immunity, particularly IL‐6, but likely type I IFNs as well.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although we could not detect type I IFN induction at the time point examined in LNs of mice with CIA, TBK‐1 inhibition has been shown to reduce the type I IFN signature and alleviate disease in the three‐prime repair exonuclease 1–knockout murine model of SLE, through inhibition of the cGAS/STING pathway . Other studies demonstrate synergies between IL‐6 and type I IFN by driving optimal Tfh cell polarization and type I IFN–dependent IL‐6 induction in DCs that supports GC‐driven affinity maturation of antibodies . Taken together, we propose that TBK‐1 inhibition reduces production of cytokines associated with humoral immunity, particularly IL‐6, but likely type I IFNs as well.…”
Section: Discussionmentioning
confidence: 61%
“…Optimal GC development and maintenance is positively regulated by type I IFNs, IL‐6, and ICOS signaling . Because TBK‐1 is a common denominator of these pathways , TBK‐1 inhibition might be therapeutically effective, even in established autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…GC area was calculated by using the surface creation module in Imaris (Bitplane). Graph plots depict the widest area for each GC present in the dLNs examined as previously described51.…”
Section: Methodsmentioning
confidence: 99%
“…For example, data from John O'Shea's laboratory indicate that IFN-a/b signaling in activated T cells directly induces Bcl6 expression through a STAT1-dependent mechanism (126). Using mixed bone marrow chimeras, Riteau and colleagues (127) demonstrated that T cellintrinsic type I IFN signaling is required for optimal Tfh cell responses following protein or peptide immunization. In another study, type I IFN signaling enhanced classswitched Ab responses to protein immunization, but this effect was prevented when T cells were IFNAR deficient (128), indicating that IFN-a/b signaling in CD4 + T cells directly promotes Tfh cell differentiation.…”
Section: The Role Of the Cytokine Milieu In Abnormal Tfh Cell Responsmentioning
confidence: 99%